Teaching Evidence-Based Physical Diagnosis: A Workshop for Hospitalists - Zahir Kanjee; Anjala V. Tess (Association of American Medical Colleges, 2022)
Introduction Teaching on physical examination, especially evidence-based physical diagnosis, is at times lacking on general medicine rounds. We created a hospitalist faculty workshop on teaching evidence-based physical diagnosis. Methods The workshop included a systematic approach to teaching evidence-based physical diagnosis, multiple teaching resources, and observed peer teaching. A long-term follow-up session was offered several months after the workshop. Participants completed questionnaires before and after the workshop as well as after the long-term follow-up session. Results Four workshops were conducted and attended by 28 unique participants. Five hospitalists attended long-term follow-up sessions. Due to the COVID-19 pandemic, repeat sessions and long-term follow-up were limited. In paired analyses compared to preworkshop, respondents after the workshop reported a higher rate of prioritizing ( p = .008), having a systematic approach to ( p < .001), and confidence in ( p = .001) teaching evidence-based physical diagnosis. Compared to before the workshop, participants after the workshop were able to name more resources to inform teaching of evidence-based physical diagnosis ( p < .001). Informal feedback was positive. Respondents noted that the workshop could be improved by allowing more practice of the actual physical exam maneuvers and more observed teaching. Discussion We created and implemented a workshop to train hospitalists in teaching evidence-based physical diagnosis. This workshop led to improvements in faculty attitudes and teaching skills. Long-term outcomes were limited by low participation due in part to the COVID-19 pandemic.